APLIKASI E-GOVERNMENT PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA DESA SUMBER MULYA KABUPATEN MUARO JAMBI: Application;E-Government;Administration;Population;Service. - Simorangkir, Lucy; Kahar, Novhirtamely; Lestari, Megaria (LP2M Universitas Nurdin Hamzah, 2022)
Desa Sumber Mulya is a village located in the North Bahar District, Muaro Jambi Regency. The population continues to grow every year in Desa Sumber Mulya along with the demands of the community both inside the village and outside the village for population administration services which of course demand to switch from a manual data collection system and population administration service to a more advanced administrative service system efficient and effective administrative data collection of its citizens. The purpose of this research is to make the population administration service system better and easier in terms of data processing. The input requirements include population data, social assistance data, and certificate data. The process needs are population data processing, social assistance data processing, and certificate data processing. Meanwhile, the output needs are in the form of population data reports and reports of certificates that have been processed previously. This web-based application is built to assist the Desa Sumber Mulya government in serving the activities of recording births, deaths, marriage certificates, and statements of introduction for family cards, identity cards, temporary resident certificates, residents moving in and out and collecting data on social assistance. So that the expected results in this study are to facilitate the population administration service system so that it is effective and efficient.